Effect of housing construction material on childhood acute respiratory infection: a hospital based case control study in Bangladesh - Jhantu Bakchi; Rosul Ahmed Rasel; Khandokar Farmina Shammi; Sumaiya Ferdous; Shamima Sultana; Mst. Rokshana Rabeya (Scientific Reports, 2024)
Abstract Despite several studies conducted to investigate housing factors, the effects of housing construction materials on childhood ARI symptoms in Bangladesh remain unclear. Hence, the study aimed to measure such a correlation among children under the age of five. A hospital-based case–control study was conducted, involving 221 cases and 221 controls from January to April 2023. Bivariate and multivariate binary logistic regression was performed to measure the degree of correlation between housing construction materials and childhood ARI symptoms. Households composed of natural floor materials had 2.7 times (95% confidence interval 1.27–5.57) and households composed of natural roof materials had 1.8 times (95% confidence interval 1.01–3.11) higher adjusted odds of having under-five children with ARI symptoms than household composed of the finished floor and finished roof materials respectively. Households with natural wall type were found protective against ARI symptoms with adjusted indoor air pollution determinants. The study indicates that poor housing construction materials are associated with an increased risk of developing ARI symptoms among under-five children in Bangladesh. National policy regarding replacing poor housing materials with concrete, increasing livelihood opportunities, and behavioral strategies programs encouraging to choice of quality housing construction materials could eliminate a fraction of the ARI burden.